Shocking safely: Intravascular lithotripsy to under expanded interwoven stent - Vanessa Irvine, MBBS; Edward Choke Tieng Chek, PhD, FRCS; Darius Aw Kang Lie, FRCS (Journal of Vascular Surgery Cases and Innovative Techniques)
Calcified lesions pose formidable obstacles in managing patients with chronic limb-threatening ischemia. Calcification impedes stent expansion, a pivotal determinant in averting restenosis and stent thrombosis. While aggressive angioplasty may alleviate these obstacles, it often fails to achieve satisfactory luminal augmentation. Intravascular lithotripsy, supported by its established safety and efficacy in coronary intervention cases series and registries, has emerged as a novel solution for persistent stent underexpansion. We adopted the concept and performed late poststent deployment intravascular lithotripsy in an underexpanded interwoven stent placed within the popliteal artery of a patient with critical limb-threatening ischemia, highlighting its potential as a transformative therapeutic option.